1991
DOI: 10.1093/carcin/12.8.1503
|View full text |Cite
|
Sign up to set email alerts
|

A new colon and mammary carcinogen in cooked food, 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP)

Abstract: 2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), which is produced during cooking and is mutagenic to bacteria and cultured mammalian cells, was found to induce high incidences of colon and mammary carcinomas in F344 rats when administered at a concentration of 400 p.p.m. in the diet for 52 weeks. Since PhIP is the most abundant of the mutagenic heterocyclic amines in cooked meat and fish, the compound might be related to malignancies of the colon and breast in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
284
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 541 publications
(294 citation statements)
references
References 0 publications
7
284
0
3
Order By: Relevance
“…A predominant HA found in cooked and particularly in welldone chicken and beef is 2 -amino-1-methyl -6-phenylimidazo [ 4,5-b] pyridine ( PhIP ) (Felton et al, 1984(Felton et al, , 1986Felton and Knize, 1990a,b;Sinha et al, 1995 ). Dietary exposure to PhIP has been shown to induce colon, intestinal and mammary adenocarcinomas in rats Ochiai et al, 1991;Ito et al, 1991Ito et al, , 1997Ghoshal et al, 1994 ), as well as prostate cancer (PC ) in rats (Shirai et al, ,1999. Another predominant HA found in cooked meats, 2 -amino-3,8-dimethylimidazo [ 4,5-f] quinoxaline (MeIQx), causes tumors at multiple sites in rats and mice Bogen, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…A predominant HA found in cooked and particularly in welldone chicken and beef is 2 -amino-1-methyl -6-phenylimidazo [ 4,5-b] pyridine ( PhIP ) (Felton et al, 1984(Felton et al, , 1986Felton and Knize, 1990a,b;Sinha et al, 1995 ). Dietary exposure to PhIP has been shown to induce colon, intestinal and mammary adenocarcinomas in rats Ochiai et al, 1991;Ito et al, 1991Ito et al, , 1997Ghoshal et al, 1994 ), as well as prostate cancer (PC ) in rats (Shirai et al, ,1999. Another predominant HA found in cooked meats, 2 -amino-3,8-dimethylimidazo [ 4,5-f] quinoxaline (MeIQx), causes tumors at multiple sites in rats and mice Bogen, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) is an environmentally abundant HCA, produced by pyrolysis of amino acids and proteins during cooking of meat and fish. 6 It is also contained in beer, wine and cigarette smoke condensate 12,13 and has been shown to induce cancers of the colon, breast 14 and prostate. 15 PhIP is found at a concentration range of 0.56-69.2 ng/g in cooked foods and daily intake is estimated to be 0.1-13.8 mg/person.…”
mentioning
confidence: 99%
“…32,33 A recent report by Sinha and colleagues 34 indicated that PhIP could be one of the causative agents for colon carcinogenesis in humans. To elucidate the biological significance of ACF in colon carcinogenesis, ACF induced in F344 male rats by PhIP were subjected to morphological and genetic analyses.…”
mentioning
confidence: 99%